2020
DOI: 10.1016/j.jaci.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The IL-37–Mex3B–Toll-like receptor 3 axis in epithelial cells in patients with eosinophilic chronic rhinosinusitis with nasal polyps

Abstract: Background: The role of IL-37, an immunosuppressive cytokine, in patients with inflammatory diseases is unclear. Objective: We sought to explore the expression and pathogenic function of IL-37 in patients with chronic rhinosinusitis (CRS). Methods: Expression levels of IL-37, IL-18 receptor a, IL-1 receptor 8, Mex3 RNA binding family member B (Mex3B), and thymic stromal lymphopoietin (TSLP) in nasal samples were studied by using quantitative RT-PCR, immunohistochemistry,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 51 publications
2
50
0
1
Order By: Relevance
“…In this issue of The Journal of Allergy and Clinical Immunology, the report published by Liu et al 6 points to an important role of IL-37 in CRSsNP and eosinophilic and noneosinophilic CRSwNP. The authors convincingly demonstrated the expression of IL-37 in nasal tissues and scraped nasal epithelial cells from patients with CRS.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…In this issue of The Journal of Allergy and Clinical Immunology, the report published by Liu et al 6 points to an important role of IL-37 in CRSsNP and eosinophilic and noneosinophilic CRSwNP. The authors convincingly demonstrated the expression of IL-37 in nasal tissues and scraped nasal epithelial cells from patients with CRS.…”
mentioning
confidence: 98%
“…The reduced IL-37 secretion in eosinophilic CRSwNP could be a consequence of reduced infiltration of macrophages, mast cells, and T and B cells that are known to produce IL-37 as well. Unfortunately, Liu et al 6 did not exclude this possibility.…”
mentioning
confidence: 99%
See 3 more Smart Citations